Power Quality Improvement Using Distribution Static Compensator (D-Statcom) On 11 Kv Distribution System - Hj.Abdul Wahab, Noor Izzri (2002)
Tile increased awareness ill power quality issues has brought tremendous changes and improvements in power electronics devices. Various circuit topologies and control techniques have been developed aimed at mitigating power quality disturbances.Custom Power concept is one of technological responses to the poor power quality presently surfacing in factories, offices and homes. It is dedicated to maintaining and improving the quality and reliability of distribution level power and to protecting customers against disturbances generated by other users in the network. Custom Power (CP) family includes power electronics based devices such as Distribution Static Compensator (D-STATCOM), Dynamic Voltage Restorer (DVR), Solid State Fault CUlTent Limiter (SSFCL), Active Power Filter (APF) and Solid State Transfer Switch (SSTS). The CP concept is the customer's solution by the utilities sector.In this research work, the focus will be on one of the CP family, that is, the D-STATCOM. The D-STATCOM, which consists of a thyristor-based voltage source inverter, uses advanced power electronics to provide voltage stabilization, power factor correction, harmonic control and a host of other power quality solutions for both utility and industrial applications. This thesis describes the configuration, design and control of the 12-pulse 0- STATCOM. Its simulation works are done by using PSCAD/EMTDC version 3.0.7 software, developed by Manitoba HVDC Research Center, Canada. The designed 0- STATCOM is connected in shunt to an 11 k V test distribution system Simulations have been carried out to illustrate the effectiveness of the D-STATCOM in mitigating voltage sags and voltage unbalance as well as eliminating harmonics. The results obtained from the simulations clearly showed that the designed D-ST ATCOM is capable in mitigating voltage sags and voltage unbalance. Furthermore, by connecting passive filters in shunt at the primary side of the step-down transformer reduces the harmonics generated by the D-STATCOM.